2022
DOI: 10.1108/ijchm-08-2021-0960
|View full text |Cite
|
Sign up to set email alerts
|

The impact of AI-enabled service attributes on service hospitableness: the role of employee physical and psychological workload

Abstract: Purpose Hospitableness lies in the center of hospitality services. With the infusion of artificial intelligence (AI) technology in the hospitality industry, managers are concerned about how AI influences service hospitableness. Previous research has examined the consequences of AI technology based on customers’ assessment while ignoring the key players in service hospitableness – frontline employees (FLEs). This study aims to reveal how AI technology empowers FLEs physically, mentally and emotionally, facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…Given the expansion of role breadth in hospitality organizations as a result of staffing shortages, our work builds upon research that investigates how to deal with volume of work (e.g. Qiu et al , 2022) to also consider the scope of work performed by employees. In providing evidence that illegitimate tasks can have important effects on both in-role and extra-role performance in hospitality employees, we advance understanding of illegitimate tasks, an understudied phenomenon in organizations (Semmer et al , 2019), and, drawing on COR theory, we advance theoretical understanding of the types of role-based stressors that may impact hospitality employees’ in-role and extra-role performance.…”
Section: Discussionmentioning
confidence: 99%
“…Given the expansion of role breadth in hospitality organizations as a result of staffing shortages, our work builds upon research that investigates how to deal with volume of work (e.g. Qiu et al , 2022) to also consider the scope of work performed by employees. In providing evidence that illegitimate tasks can have important effects on both in-role and extra-role performance in hospitality employees, we advance understanding of illegitimate tasks, an understudied phenomenon in organizations (Semmer et al , 2019), and, drawing on COR theory, we advance theoretical understanding of the types of role-based stressors that may impact hospitality employees’ in-role and extra-role performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, enhanced innovative behaviors were observed when AI was applied to support job autonomy, job complexity, specialization, and information processing (Verma & Singh, 2022). In a service work context, AI can enhance workers' resources by reducing mental and physical fatigue and increasing positive emotional states (Qiu et al, 2022). Such outcomes are also facilitated by AI developers effectively combining machine intelligence and human domain expertise, in conjunction with those human experts, to create a human–machine learning hybrid work practice (van den Broek et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in this stream are on management optimization and antecedents to users' satisfaction with AI applications. For example, Qiu et al (2022) discovered that the anthropomorphic, functional and informational aspects of AI technologies reduced employees' physical and mental fatigue, thereby improving overall service quality. Jim enez- Barreto et al (2021) found that self-determined interaction (e.g.…”
Section: Resultsmentioning
confidence: 99%